The impact of sub-metering requirements on building electrical systems design - Clements, Derek (Kansas State University, 2020)
New energy codes and standards, including ANSI/ASHRAE/IES Standard 90.1: Energy Standard For Buildings Except Low-Rise Residential Buildings (ASHRAE 90.1), LEED and UK Building Regulations Type Part L2 have adopted requirements for electrical sub-metering to be installed within commercial buildings. It is no longer acceptable to only meter total building usage. Separate sub-meters must be installed to monitor where and how power is utilized within commercial buildings. The information provided by the use of these sub-meters can reduce energy usage in the building by informing building owners and occupants of how and where they are using the most energy, by alerting building owners to potential operating and/or maintenance issues and by identifying energy efficiency measures through the use of a building energy audit. This paper identifies the requirements outlined in ASHRAE 90.1, LEED and the UK Building Regulations Part L2. The paper also identifies products and methods to integrate sub-metering into the electrical systems design as well as benefits to separately metering mechanical, electrical and receptacle loads within a building. A case study for a fictitious building is provided, identifying design solutions and costs associated with a sub-metering system meeting the requirements of ASHRAE 90.1.
Keywords: Submetering; Sub-metering; Electric; ASHRAE 90.1; LEED